Factors influencing Malaysian youth's intention to purchase fast fashion products - Loo, Ying Wing; Osman, Syuhaily; Lau Leby, Nur Jasmine (Human Resource Management Academic Research Society, 2023)
This study discovers the consumer behaviour of Malaysian youth towards fast fashion to understand factors that influence their purchase intention. The significance of this study is it contributes quantitatively to the field of fast fashion and consumer behaviour in Malaysia, which is limited as of this study. Past studies in the field have shown consumers of various countries and culture behave differently towards fast fashion. Five factors (brand sustainability, trendiness of product, social factor, product accessibility and affordable pricing) have been identified from past literatures on fast fashion to be integrated with the main components of TPB to find out which factor is the best predictor of Malaysian youth’s purchase intention. A total of 384 respondents had participated in the online survey containing instruments adapted from multiple studies. The study’s findings revealed that trendiness of product has the strongest influence on youth’s purchase intention, while social factor is the least receptive factor to them. The five factors have a significant relationship with purchase intention and the relationship is overall positive. As recommendation for future studies, this quantitative study can be extended to bigger and diverse demographics, as well as other regions of Malaysia.